Keterampilan Komunikasi Interpersonal Konselor terhadap Pemahaman Pelecehan Seksual Peserta Dialog Komunitas - Ita Erviana (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2023)
Background: Sexual harassment and violence cases in Indonesia in 2022 was 338,496 cases. It was recorded by the Commission on Violence against Women. Objective: This study aims to determine the interpersonal communication skills of peer counselors in understanding sexual harassment of community dialogue participants. Method: The method used is descriptive qualitative because it can describe and explore the phenomenon thoroughly. Data collection was obtained from interviews, observations, and documentation which were then analyzed by reducing data, presenting data, and drawing conclusions. The data sources in this research are primary data and secondary data. Primary data are the results of interviews with managers, peer counselors, and community dialogue participants, while secondary data are minutes of community dialogue activities and PKBI Central Java Pilar files. The validity of the data in this study uses source and method triangulation techniques and reference materials. Result: The results of this study indicate that the interpersonal communication skills of peer counselors are good based on existing communication skills indicators. This is evidenced during the community dialogue, the participants were enthusiastic and interactive in the discussion because the peer counselor opened the session very well so that the participants were open, besides that the participants also easily understood the information conveyed by the peer counselor because of good communication and interesting methods. Peer counselors have fulfilled all seven indicators of interpersonal communication skills, where these skills are a factor in the success of the community dialogue objectives..